Alzheimer’s Disease Hypothesized as Type 3 Diabetes: A Review - Manjeet K Gill-Sharma (Disease and Health: Research Developments Vol. 9, 2025)
The precise connection between Alzheimer’s disease (AD) and type 2 Diabetes is still being debated. However, poorly controlled blood sugar may increase the risk of developing AD. Due to this strong relationship, some have referred to AD as ‘Diabetes of the brain’ or ‘type 3 Diabetes’ (T3D). Diabetes mellitus (DM), type1 (T1D) and type2 (T2D) are diseases of the peripheral organs, characterized by relative Insulin deficiency, caused by decreased synthesis or reduced signalling of Pancreatic Insulin. Recently, Alzheimer’s disease has been hypothesized to be type 3 Diabetes (T3D), deemed to be characterized by Insulin resistance. Presumably, Insulin resistance can be attributed to hyperinsulinemia, hyperlipidemia or pro-Inflammatory cytokines, through down-regulation or desensitization of cerebral Insulin receptors (IR). Brain is absolutely dependent upon glucose as fuel for ATP biosynthesis. Insulin receptor (IR), the central moiety, implicated in both DM and AD, is expressed from a single gene located on human chromosome 19p 13.2-19p 13.3. Although IR is involved in the cognitive decline of both DM and AD, the receptor subtypes in the brain and peripheral tissues differ in structure and function. Glucose uptake in the brain is mostly Insulin-independent, unlike the peripheral organs, with the exception of Insulin-sensitive neurons, in view of its absolute dependence. While the Insulin-dependent glucose uptake in the neurons depends upon the translocation of glucose transporter4 (GlUT-4) to the plasma membrane, Insulin-independent, cerebral uptake depends upon vascular-endothelial-cell glucose transporter1 (GlUT-1) and neuronal glucose transporter3 (GlUT-3). Glucose-sensitive, neuron-specific, GLUT-8 can translocate to the endoplasmic reticulum membrane, and pull out glucose, in order to maintain intra-neuronal glucose levels. Besides IRs, brain also expresses receptors for Adipokine and leptin (LR) that cross-react with IR, in neurons that co-express these receptors. Cerebral IRs and LRs subserve alternative roles in synaptic functions and cognition. Whereas AD and DM are characterized by dementia and cognitive decline, respectively, their known cellular biomarkers are different, namely, neuronal Amyloid Peptide (AP\(β\)) ), TAU, glial TDP-43 for AD and Islet Amyloid Polypeptide (IAPP) for DM. DM also has a genetic component, namely, HLA-DQB1, CTLA-4, INS genes. Whereas Insulin supplementation has therapeutic benefits for peripheral organs, the same does not hold true for Central Nervous System (CNS). IR, LR and GlUT-4 are co-expressed in a subset of neurons, where Leptin acts as an inhibitor of Insulin signalling. Thus, hyperleptinemia can also contribute to Insulin resistance through cross-reactivity with Insulin receptors, in GLUT-4-positive neurons. It can be surmised that the overlap between AD and DM is restricted to Insulin resistance but not glucose uptake or availability. It is suggested that, despite the overlapping features, Alzheimer’s disease may not meet the requirements of the so-called, type 3 Diabetes (T3D). The mechanism underlying peripheral Insulin resistance of DM involves desensitization of IR and reduced glucose uptake. The mechanism underlying the deemed, cerebral Insulin resistance of AD is yet a moot point. Further research is required to validate the findings of earlier studies, examine alternative etiologies and devise effective treatments for AD.